The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/1040638712462377
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility patterns ofCrossiella equiandAmycolatopsisspecies causing nocardioform placentitis in horses

Abstract: Nocardioform actinomycetes are significant causes of placentitis and abortions in horses. In the current study, antimicrobial susceptibility patterns of 38 Amycolatopsis spp. and 22 Crossiella equi isolates, the most common nocardioform actinomycetes causing placentitis in horses, were evaluated. Antimicrobial susceptibilities of these isolates were tested by broth microdilution method in a commercial system, which was designed for Nocardia spp., fast-growing Mycobacterium spp., and other aerobic actinomycetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Another study reported that all Gram‐negative bacterial isolates from equine neonates had an MIC 90 of 4 μg/mL. Orsini et al measured just 6 isolates that had MIC that varied from 0.5 to 128 μg/mL, and finally Erol et al reported that nocardioform actinomycetes had an MIC 90 of 32 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that all Gram‐negative bacterial isolates from equine neonates had an MIC 90 of 4 μg/mL. Orsini et al measured just 6 isolates that had MIC that varied from 0.5 to 128 μg/mL, and finally Erol et al reported that nocardioform actinomycetes had an MIC 90 of 32 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…A swab from each chorioallantois was collected and cultured according to Erol et al . . Polymerase chain reactions for C.equi and Amycolatopsis spp.…”
Section: Methodsmentioning
confidence: 99%
“…In this experiment, each inoculum contained 1 × 10 9 cfu of C. equi . Detailed explanation of the bacterial culture is described elsewhere and in the Supporting information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations